Effects of Kinesio Taping Alone Versus Sham Taping in Individuals with Musculoskeletal Conditions After Intervention for at Least One Week: A Systematic Review and Meta-Analysis - Garcia-Hermoso, A; Hormazabal-Aguayo, I (Elsevier Ltd, 2019)
Background: Kinesiotaping (KT), has emerged as an interesting and relatively novel method for treating musculoskeletal conditions. To date, none of the systematic reviews with meta-analysis have addressed the efficacy of KT alone (without any other intervention) over sham taping (ST). Objective: The present meta-analysis aimed to investigate the effectiveness of KT versus ST in patients with musculoskeletal conditions in interventions lasting at least 1 week on musculoskeletal conditions and functional performance outcomes. Data source: Manual and electronic searches (CENTRAL, EMBASE, MEDLINE and PEDro) were conducted using kinesiotaping, strapping, musculoskeletal pain and musculoskeletal conditions. Study selection criteria: Randomised controlled trials on adults with a diagnosis of musculoskeletal conditions. Data extraction and data synthesis: Two researchers independently carried out the search and the third author was referred to for arbitration. The methodological quality of the studies using the PEDro scale and GRADE approach. Results: Six RCTs were identified and included in the meta-analysis. When compared with ST in adults with chronic non-specific low-back pain (LBP), KT resulted in superior effects on pain at follow-up, but the pooled pain in the immediate post-treatment period and disability scores (in the immediate post-treatment period and at follow-up) were not significantly different. Generally, all results were supported by low quality evidence according to GRADE criteria. Conclusion: Our findings indicate inconclusive and low-quality evidence of a beneficial effect of KT alone over ST in LBP and knee osteoarthritis. Systematic review registration number: PROSPERO CRD42018084151. © 2019 Chartered Society of Physiotherapy